Sit and be fit. All-sitting exercise video [videorecording (DVD)] - Lawrence, Bob; Wilson, Mary Ann (Sit and Be Fit, 2005)
An exercise program consisting of slow, gentle motions designed for those who have difficulty standing or are wheelchair bound.